RELIGIOUS TEACHERS' ROLE IN DEVELOPING SOCIAL SKILLS AMONG HIGH SCHOOL STUDENTS: APPLYING VYGOTSKY'S THEORY IN AN INTEGRATED EDUCATIONAL ENVIRONMENT - Muthahari, Ali; Dewantoro, Mohammad Hajar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to investigate the role of religious teachers in facilitating the socio-developmental tasks of adolescents at MA Wahid Hasyim. The approach employed integrates Vygotsky's theory, which emphasizes the significance of social interaction in learning, with the pesantren tradition, focusing on character development grounded in religious values. In the modern educational context, religious teachers play a pivotal role in guiding students through the process of social development, particularly in helping them attain age-appropriate social maturity. Employing a combination of surveys and interviews, this research involved 30 students aged 16-18 from grades 10 to 12 as participants. Preliminary findings indicate that religious teachers play a significant role in fostering a supportive environment for positive social interaction, however, the study has yet to fully explore the extent to which students have achieved the desired level of social maturity. Future research is needed to delve deeper into the level of social maturity among students within the pesantren educational context and its implications for their future development.